SP0019 How the clinician can use the cochrane library. (1st June 2001) - Tugwell, P; McGowan, J; Welch, V; Shea, B; Wells, G
Abstract : Objectives: To demonstrate online searching of The Cochrane Library for clinicians and illustrate how The Cochrane Library can be used in practice. The Cochrane Library is the single best source of updated systematic reviews of health care interventions. There are now 37 published Cochrane reviews relating to Musculoskeletal Diseases. The abstracts can be accessed for free on the internet and lay summaries written in consultation with consumers are also available on the internet (www.arthritis.ca ). The first part of this workshop will demonstrate how to use text words to search for consumer and scientific abstracts available for free on the internet. In addition, the web interface for the full Cochrane Library will be shown. The second purpose of this workshop is to provide examples of how to use Cochrane reviews in clinical practice. For example, the University of Ottawa has developed hospital-wide access to the Cochrane Library, and these can be accessed by clinicians from any computer with an internet connexion. The pooled estimate of efficacy and side effects is the best estimate from all published randomised controlled trials. The direction and statistical significance of this estimate can be easily interpreted. The second part of the workshop will illustrate the interpretation of the magnitude and direction of the pooled estimate. In addition, the workshop will illustrate how these estimates can be used as part of evidence based practice.